Resilience and The Character of Student Curiosity in Discovery Learning-Based Online Learning - Prasetyo, Adirasa Hadi; Jasiah, Jasiah; Idriyani, Natris; Setyawati, Sri Panca (International Journal of Applied Guidance and Counseling, 2022)
The Covid 19 pandemic has had many impacts on various sectors of human life. The education sector is also feeling the effects of the pandemic that hit almost all parts of the world. Learning that initially takes place in the classroom turns into online learning. This article was written using a literature study approach. The data obtained comes from similar articles from various sources in national journals. The use of discovery learning models in online learning can be done in many ways. For example: the teacher gives a picture of the problem to the student to be examined comprehensively. After students can find and think deeply about the material with the attachment of discovery learning. Of course, the material conveyed through the picture must be creative in order to match the character of students' curiosity. In addition, the delivery of material can be delivered by utilizing the LMS (Learning Management System) platform, such as: edmodo, schoology, google classroom and so on. This learning design aims to make students have an attitude of resilience to the covid 19 pandemic that is sweeping around the world today.